Possibilities of Computed Tomography in the Planning of Inferior Vena Cava Resection in Patients with Liver Alveococcosis - A. N. Bashkov; Zh. V. Sheykh; S. E. Voskanyan; A. P. Dunaev; M. V. Popov; E. V. Naydenov; M. V. Shabalin; A. S. Safonov (Вестник рентгенологии и радиологии)
Objective.  To estimate the informative value of computed tomography (CT) in the planning of inferior vena cava (IVC) resection in patients with alveococcosis of the liver on the basis of the extent of contact of parasitic masses with its wall around the circumference.Material and methods. CT studies and surgery protocols were retrospectively analyzed in patients with liver alveococcosis in the period between 2014 and 2017.Results. The CT-measured extent of contact of parasitic masses along the circumference of IVC was compared with the intraoperative pattern for its involvement and with resection volume data. CT findings show that circular resection was not required in contact of parasitic mass with the IVC wall  over a 90° stretch; the resection could be performed in 29, 86, and 100% of patients in contact over 180, 270, 360° stretches, respectively.Conclusion. CT can assess whether there may be IVC invasion when planning a surgical intervention.  The threshold value of the extent of contact of parasitic masses with IVC, as evidenced by CT, is 180°, at which the possibility of circular resection and vein prosthesis should be considered.